Not Just an Undergraduate Issue: Campus Climate and Sexual Violence Among Graduate Students - McMahon, Sarah (Journal of interpersonal violence, 2021)
The lack of research on graduate students’ experiences with campus sexual violence and the campus climate is a glaring gap in the literature (Bonistall Postel, 2020). Thus, the current exploratory study examines the experience of graduate students at one university to determine their victimization rates and the number of disclosures they receive from peers. In addition, we compare graduate and undergraduate students’ awareness of resources on campus and their confidence in knowing where to seek assistance for their peers or themselves. Finally, we compare key influential factors related to the campus climate such as sense of community and perceptions of the university’s responsiveness to incidents of sexual violence among graduate and undergraduate students. An online survey was administered to a sample of 9,546 students, with 79.9% undergraduates and 20.1% graduates. A total of 5.2% of graduate students reported experiences of sexual violence since attending the university, with 13% receiving disclosures from peers. MANCOVA revealed that compared with undergraduate students, graduate students had significantly less awareness of campus resources, less confidence in knowing where to seek assistance, and less of a sense of community. There were no differences in perceptions of the university’s handling of sexual violence. The findings highlight the importance of including and targeting graduate students in sexual violence awareness and prevention programming on college campuses.